THE DEVELOPMENT OF EDUTAINMENT LEARNING MODEL IN SOCIAL SCIENCE EDUCATION/IPS Research and Development Study on IPS education at elementary level in Bandung and Cimahi - Kusmarni, Yani (Universitas Pendidikan Indonesia, 2016)
This research is Entitled â€œThe Development of Edutainment Learning Model in Social Science Education/IPS (Research and Development Study on IPS education at elementary level in Bandung and Cimahi)â€is created to gain a model based on developing learning process in the classroom. This research is also based on the importance of teachersâ€™ creativity in making a fun learning yet still accommodating for the achievement of compentences. Various innovation on IPS education in contextual study have been grown in school and varsity level, it makes various methods have been created by the teachers. However, those innovation still lacks in the accommodating students to reach the competence expected to them. This research will analyze, process, and describe various innovation in IPS learning which are based on Edutainment, which will be conducted in Elementary School (SD/SMP) in Bandung and Cimahi. The focus will be on describing the competences achievement based on the Edutainment learning model. The Competence of Passing Students (Kompetensi Pencapaian Lulusan) is not based on Cognitive aspect only. It needs applicable development of skills. This research uses Research and Development Study which has been begun on this first step which is Descriptive Study which trying to develop critical thinking through Edutainment. tthis research, hopefully there will be a product which is an education model for elementary level which is able to develop an innovation in IPS learning to help studetns develop their critical thinking.Â Key Words : Edutainment model, Elementary level of IPS education,Critical ThinkingÂ